The application of sports psychology in overcoming performance anxiety among Italian cyclists - Li, C.; Zhang, W. (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2024)
The aim of the research is to determine the applications related to sports psychology in overcoming performance anxiety among Italian cyclists. Athletes, particularly cyclists, frequently struggle with performance anxiety, which can seriously impair their capacity for peak performance. In this abstract, we investigate the use of sports psychology strategies designed specially to help Italian cyclists who experience performance anxiety. The research was based on primary data analysis to determine whether it used smart PLS software and generated results that included descriptive statistics, correlation coefficient analysis, and the smart PLS Algorithm Model between them. This research study offers a methodical strategy made up of several psychological treatments meant to reduce performance anxiety and enhance performance. It discusses many techniques, including biofeedback, stress management, goal setting, cognitive restructuring, visualization, pre-performance rituals, simulated pressure scenarios, and creating a supportive team atmosphere. By practicing these tactics, Italian riders can acquire the psychological fortitude required to negotiate stressful competition situations successfully. the overall research It is vital to constantly assess and modify treatments to make sure they are efficient and meet the demands of each athlete. Italian cyclists may overcome performance anxiety and reach their full potential on the bike by incorporating sports psychology concepts into their training program, which will help them succeed in national and international contests.